Varicella associated pneumoniae in a pediatric population - Elena Bozzola; Guido Castelli Gattinara; Mauro Bozzola; Nadia Mirante; Marco Masci; Chiara Rossetti; Andrzej Krzystofiak; Luciana Nicolosi; Renato Cutrera; Laura Lancella; Alberto Eugenio Tozzi; Alberto Villani (BMC, 2017)
Abstract Background Varicella pneumonia has been studied extensively in adults; it may also affect children and may require hospitalization. Methods We examined pneumonia complications in children hospitalized for varicella, over a 13 year period. Results Pneumonia occurred in 8.2% of children hospitalized for varicella. The median length of hospitalization was 6 days. No statistically significant difference in length of stay was detected between immunodepressed children and previously healthy children. The hospitalization was on average shorter in patients who started antiviral therapy within 24 h of varicella onset. None of the included patients had been previously immunized for varicella. Conclusions Our results support the need for increased awareness of current varicella prevention recommendations among both immunocompetent and immunodepressed individuals. In children affected by varicella, prompt antiviral therapy may be indicated to reduce the number of days of hospitalization.